P36 Ethnic differences in Composite Physiologic Index (CPI) in pulmonary sarcoidosis: a 10-year experience in a specialist sarcoidosis clinic. (12th November 2015) - Tully, T; Galloway, J; Lally, J; Silber, E; Brex, P; Walsh, S; Larkin, G; Barker, J; Birring, S
Abstract : Introduction and objectives: CPI has been reported to be an accurate predictor of mortality in sarcoidosis and IPF. A CPI score of >40 is associated with a 5 year survival probability of 50%. 1 There is a paucity of studies of CPI in patients of black ethnicity. We investigated CPI in a large cohort of patients attending a specialist sarcoidosis clinic serving a large African Caribbean community in South-East London. Methods: 503 subjects with a diagnosis of sarcoidosis were assessed between May 2005 and May 2015. Relevant data needed to calculate CPI and ethnicity information was available in 297 patients with pulmonary involvement (based on radiological evidence +/- histological evidence). We calculated CPI with the following formula: 91·0 – (0·65 × percent predicted DLCO) – (0·53 × percent predicted FVC) + (0·34 × percent predicted FEV1). Clinical demographics, organ involvement, lung function, histology and subsequent therapy were systematically recorded (Table 1 ). Results: There were significant differences in CPI between all ethnic groups (ANOVA, p < 0.001). Black patients had a higher mean CPI score compared to white patients (39.0 (14.2) vs 29.9 (18.5), t = -4.129, p < 0.001) (Table 1 ). CPI was significantly higher in black Caribbean patients versus black African patients (41.2 (14.4) vs 36.3 (13.7), t = 2.656 p = 0.008). CPI was weakly correlated with number of immunosuppressant medications used; correlation coefficient r = 0.214, p < 0.001. CPI was not associated with age at presentation, gender, initial requirement of treatment or prediction of ≥2-organ involvement. Conclusion: Black patients have more severe disease than other ethnicities, with the most severe illness in those of black Caribbean ethnicity, who have the worst CPI scores. Further studies are needed to determine the long-term outcome in this patient cohort, such as decline in PFTs, quality of life and mortality. Reference: 1 Walsh SL, Wells AU, Sverzellati N, et al . An integrated clinicoradiological staging system for pulmonary sarcoidosis: a case-cohort study. Lancet Respir Med . 2014;2 :123–130